Bacterial and archaeal taxa are reliable indicators of soil restoration across distributed calcareous grasslands. (27th May 2020) - Armbruster, Melanie; Goodall, Tim; Hirsch, Penny R.; Ostle, Nick; Puissant, Jeremy; Fagan, Kate C.; Pywell, Richard F.; Griffiths, Robert I.
Abstract: Land‐use intensification can reduce soil carbon stocks and changes microbial community biodiversity and functionality. However, there is a lack of consensus on whether management consistently affects microbial biodiversity across geographic scales, and how this relates to altered soil function. From a regulatory and monitoring perspective, there is a need to identify functionally relevant indicators of land use in order to evaluate the progress of soil restoration approaches. We performed a landscape‐scale survey of unimproved calcareous grasslands paired with local arable contrasts, and assessed the consistency of responses in a variety of soil, biotic and functional measures. In addition, adjacent grasslands undergoing restoration were assessed to identify soil microbial indicators of recovery. Organic matter content was consistently larger in grasslands than in arable fields, and increased with time in the restoring sites. Molecular comparisons of grassland versus arable soils revealed numerous bacterial, archaeal and fungal indicators, with more representatives of Ca. Xiphinematobacter, DA101, Bradyrhizobium, Rhodoplanes, Mycobacteria and Mortierella in old grassland soils, whereas Nitrososphaera, Sporosarcina and Alternaria infectoria were more abundant in arable soils. Extracellular enzymatic responses were more variable, with none of the eight investigated enzymes being consistent indicators of grassland or arable soils. Correlation analyses, incorporating the molecular and enzymatic responses across all surveyed soils, revealed that molecular indicators were more strongly correlated with soil organic matter increases with restoration of arable soils. Our results highlight that microbial taxa are among the most sensitive indicators of soil restoration, and we identify consistent responses of specific taxa to management across geographic scales. This discovery will be important for both the instigation and monitoring of soil restoration. Highlights: Soil microbes are key drivers of soil ecosystem services and are affected by management Calcareous grassland exhibited abundant Verrucomicrobia; cropping increased Nitrososphaera These taxa responded to SOM increases with grassland restoration, more so than enzymes and fungi Microbes provide consistent, site‐independent indicators for calcareous grassland soil function restoration